Murine models of clonal haematopoiesis to assess mechanisms of cardiovascular disease. Issue 6 (23rd June 2021) - Wang, Ying; Sano, Soichi; Ogawa, Hayato; Horitani, Keita; Evans, Megan A; Yura, Yoshimitsu; Miura-Yura, Emiri; Doviak, Heather; Walsh, Kenneth
Abstract: Clonal haematopoiesis (CH) is a phenomenon whereby somatic mutations confer a fitness advantage to haematopoietic stem and progenitor cells (HSPCs) and thus facilitate their aberrant clonal expansion. These mutations are carried into progeny leucocytes leading to a situation whereby a substantial fraction of an individual's blood cells originate from the HSPC mutant clone. Although this condition rarely progresses to a haematological malignancy, circulating blood cells bearing the mutation have the potential to affect other organ systems as they infiltrate into tissues under both homeostatic and disease conditions. Epidemiological and clinical studies have revealed that CH is highly prevalent in the elderly and is associated with an increased risk of cardiovascular disease and mortality. Recent experimental studies in murine models have assessed the most commonly mutated 'driver' genes associated with CH, and have provided evidence for mechanistic connections between CH and cardiovascular disease. A deeper understanding of the mechanisms by which specific CH mutations promote disease pathogenesis is of importance, as it could pave the way for individualized therapeutic strategies targeting the pathogenic CH gene mutations in the future. Here, we review the epidemiology of CH and the mechanistic work from studies using murine disease models, with a particular focus on the strengths and limitations of these experimental systems. We intend for this review to help investigators select the most appropriate models to study CH in the setting of cardiovascular disease.